Building Historical Narratives: The Development of Virtual Reality Learning Media for Exploring Historical Sources Bung Hatta's Birthplace - Ofianto, Ofianto; Ningsih, Tri Zahra; Mulyani, Fini Fajri; Putri, Suci Kurnia (Society of Visual Informatics, 2024)
The shortcomings in the history of education, constrained by conventional teaching approaches, inadequate utilization of historical sites, and logistical hurdles, diminish student engagement and comprehension. This study aims to develop a virtual reality (VR) learning medium around Bung Hatta's birth house, aiming to enhance students' historical understanding through captivating and immersive experiences. We adapted the Borg and Gall development model into four phases: preliminary study, strategic planning, development, and validation. We utilized 360-degree pictures in conjunction with extensive historical data regarding Bung Hatta's birthplace, integrating these elements into an immersive virtual reality environment. We used expert validation to guarantee material accuracy, subsequently doing practical testing with history educators and students to evaluate usability and overall effectiveness. The findings revealed a practicality score of 87%, highlighting the substantial influence of VR media on enhancing student motivation and understanding of historical material. This technology facilitates the virtual investigation of significant historical locations, effectively surmounting geographical and financial barriers and enhancing accessibility, engagement, and the relevance of history for learners. This method enhances critical thinking and deepens appreciation of national heritage while offering a strong framework for incorporating VR into educational curricula. Further research must examine the long-term impacts of VR on various learning outcomes and its relevance across the educational curriculum. Moreover, integrating VR technology in diverse historical disciplines may augment its effectiveness and applicability in education. Virtual reality techniques improve students' understanding of history while strengthening 21st-century skills such as critical thinking and creativity